SOCIAL RESPONSIBILITY OF BUSINESS IN TIMES OF CRISIS: LESSONS FROM THE RUSSIAN-UKRAINIAN CONFLICT (Development Service Industry Management, 2024)
The article examines a number of examples of red blood cells in action and relevant factors that should be considered when developing a response to a situation. RBC also looks at how a network of national points of contact for Responsible Business Management can support business responsiveness and create a supportive environment for effective RBC both during war and reconstruction. Together, RBC, both through its standards and through its institutional capacity, provides a number of opportunities for businesses and policy makers to contribute to strengthening Ukraine's economic sustainability in very difficult circumstances.In order for the principles and standards to contribute significantly to global sustainability, it is important to take measures to protect their integrity through consistent global application across geographic regions and supply chains. Although the specific circumstances of Russia's war against Ukraine are unique, armed conflict unfortunately remains a constant part of world affairs, particularly in many other regions integrated into global value chains. In this context, RBC plays an important role in mitigating conflict-related negative impacts and other systemic risks, while at the same time enabling businesses to remain engaged and contribute to achieving sustainable development outcomes in high-risk areas where conditions permit.
Keywords: social responsibility; business; crisis conditions; Russian-Ukrainian conflict; RBC (responsible business conduct)